2008
DOI: 10.1038/nrn2499
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin, the proteasome and protein degradation in neuronal function and dysfunction

Abstract: Eukaryotic protein degradation by the proteasome and the lysosome is a dynamic and complex process in which ubiquitin has a key regulatory role. The distinctive morphology of the postmitotic neuron creates unique challenges for protein degradation systems with respect to cell-surface protein turnover and substrate delivery to proteolytic machineries that are required for both synaptic plasticity and self-renewal. Moreover, the discovery of ubiquitin-positive protein aggregates in a wide spectrum of neurodegene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
368
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 448 publications
(381 citation statements)
references
References 145 publications
10
368
0
3
Order By: Relevance
“…The ubiquitin protein system plays an essential role in the regulation of membrane and cellular proteins, and has often been referred to as the "kiss of death" due to its labeling of proteins for degradation by proteases (Petroski, 2008;Tai and Schuman, 2008). The major function of the ubiquitin protein complex is to assure intracellular protein degradation by ubiquitination; a highly complex process involving a set of successive enzymes: E1 (ubiquitin activating enzymes), E2 (ubiquitin-conjugating enzymes), E3…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitin protein system plays an essential role in the regulation of membrane and cellular proteins, and has often been referred to as the "kiss of death" due to its labeling of proteins for degradation by proteases (Petroski, 2008;Tai and Schuman, 2008). The major function of the ubiquitin protein complex is to assure intracellular protein degradation by ubiquitination; a highly complex process involving a set of successive enzymes: E1 (ubiquitin activating enzymes), E2 (ubiquitin-conjugating enzymes), E3…”
Section: Introductionmentioning
confidence: 99%
“…Postsynaptic functions are regulated by finely tuned turnover of the synaptic proteins via the ubiquitin-proteasome system (UPS) (13). We have previously shown that mutant UBQLN2 impairs the UPS in vitro (2).…”
Section: Impairment Of Ubiquitin-proteasome System In Ubqln2 P497h Trmentioning
confidence: 99%
“…Further collection of cases with similar characteristics and screening of deletion/mutations of UBE2A in syndromic as well as idiopathic XLMRaffected males, especially those mapped to areas encompassing UBE2A, will be needed to determine the significance and frequency of alterations of this gene as a causative gene for XLMR. Although, several mutations in ubiquitination and proteasome function-related genes, especially in E3 ligase genes, are involved in human neurological disorders, such as UBE3A (Angelman syndrome), PARK2 (recessive juvenile Parkinson disease), UBR1 (Johanson-Blizzard syndrome), NHLRC1 (Lafora's disease) and CUL4B, BRWD3 and HUWE1 (XLMR), 8 UBE2A is the only E2 gene known to be associated with a neurological disease. It will be also necessary to assess whether the mutation or deletion of E2 genes other than UBE2A leads to neurodevelopmental anomalies.…”
mentioning
confidence: 99%